Efficacy and safety of splenectomy in adult autoimmune hemolytic anemia - Giudice Valentina; Rosamilio Rosa; Ferrara Idalucia; Seneca Elisa; Serio Bianca; Selleri Carmine (Open Medicine, 2016)
Autoimmune hemolytic anemia (AIHA) is a rare hematologic disease, primarily affecting adults or children with immunodeficiency disease. First-line therapy consists of long course of steroids administration, with an early complete response rate (CRr) of 75-80%, but up to 20-30% of patients requires a second-line therapy. Rituximab is the first choice in refractory old AIHA patients, because of its safety and efficacy (early CRr at 80-90% and at 68% at 2-3 years). For this reason, splenectomy is even less chosen as second-line therapy in elderly, even though laparoscopic technique decreased complication and mortality rates. However, splenectomy can be still considered a good therapeutic option with a CRr of 81% at 35.6 months in patients older than 60 year-old, when rituximab administration cannot be performed.